PENDIDIKAN DAN PENYULUHAN TENTANG PENANGANAN DIABETES MELLITUS DENGAN GAYA HIDUP SEHAT - lukman hakim; mohammad ubaidillah faqih (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2023)
Diabetes Mellitus is one of the most common and serious chronic diseases in Indonesia today. Half of Diabetes Mellitus cases go undiagnosed because in general diabetes is not accompanied by symptoms until complications occur. The prevalence of diabetes is increasing due to changes in lifestyle, increase in the number of calories eaten, lack of physical activity and the increasing number of elderly population. In terms of anticipation for the prevention of Diabetes Mellitus, what really needs to be considered is to provide health education to people with Diabetes Mellitus. Health education to people with diabetes mellitus is a very important thing in the regulation of blood sugar in people with Diabetes Mellitus and preventing or at least inhibiting the emergence of chronic complications and acute complications that sufferers fear. In this case, good cooperation is needed between Diabetes Mellitus sufferers and their families with managers/extensionists who can consist of doctors, nurses, nutritionists and other staff.